THU0172 Symptomatic Subcutaneous Anti-Tumor Necrosis Factor-Treated Rheumatoid Arthritis Patients Respond to Golimumab following an Active Switch. (10th June 2014) - Huffstutter, J.E.; Kafka, S.; Brent, L.H.; Matucci-Cerinic, M.; Tang, K.L.; Wang, J.; Decktor, D.D.; Chevrier, M.; Sprabery, T.; DeHoratius, R.
Abstract : Objectives: GO-SAVE is a Ph3b, multi-center, switch assessment of SC and IV golimumab (GLM) in RA pts who have inadequate disease control despite treatment with etanercept (ETN) or adalimumab (ADA). Primary objective is to assess the efficacy of GLM at wk14 in pts with active RA and an inadequate response to ETN or ADA. Methods: Pts with active RA (DAS28 score ≥3.6 with ≥6 swollen and ≥6 tender joints) who were currently receiving MTX and ETN or ADA were switched to GLM. Pts entered the screening period 6wks prior to receiving GLM (wk -6), remained on their original anti-TNFa, and re-screened again at wk 0. All eligible pts were actively switched to open-label GLM 50mg SC q4w at wk0. At wk16, pts who achieved a good DAS28-ESR response continued to receive open-label GLM 50mg SC q4wks +MTX through wk48 (Grp 1). Those with DAS28-ESR response classified as moderate or nonresponse were randomized (1:2) to double-blind treatment grps: GLM 50mg SC q4wks + MTX (Grp 2a) or GLM 2mg/kg IV q8wks (with a loading dose at wk20) +MTX (Grp 2b). Efficacy and safety evaluations were conducted through wk52. Results: 433 pts were enrolled at wk0. All were included in the mITT population analysis. 358 pts (82.7%) were female; mean age was 55.7±11.5 yrs and mean disease duration was 10.7±9.8 yrs. At baseline, mean ± SD number of swollen and tender joints was 18.4±11.8 and 31.3±17.0, resp, and mean DAS28-ESR score was 6.2±0.9. Prior to GLM, 174 (40.2%) pts had received only ETN, and 186 (42.9%) had received only ADA; 73 (16.8%) pts had been previously exposed to both ETN and ADA, but not concomitantly. At wk14, 151 of the 433 pts (34.9%; 95% CI: 30.4%, 39.4%) achieved the primary outcome of an ACR20 response; a moderate or good EULAR response was achieved in 224pts (51.7%; 95% CI: 47.0%, 56.4%) with a mean DAS28-ESR improvement of -1.5 (95% CI: -1.6, -1.3, p<0.001) from baseline. 350 pts were treated from wk16 to wk52; 75 (21.4%) in Grp1 and 275 (78.6%) in Grp2 (91 in 2a and 184 in 2b). 42.8% (71/166) of pts in the SC Grps combined had an ACR20 and 57.2% (95/166) had a moderate or good EULAR response at wk52. Among all pts, a moderate or good EULAR response was maintained to wk52 in 52.3% (183/350), and ACR20 response was maintained to wk52 in 35.7% (125/350). During the blinded treatment interval (wk16 – 52), no significant difference was observed in EULAR responses relative to wk 16 between Grps 2a (SC) and 2b (IV). Through wk48, 246 of the initial 433 enrolled pts completed study injections/infusions. 358 (82.7%) of the 433 pts experienced AEs, and 35 pts (8.1%) experienced SAEs. Injection site reactions were reported in 10 (2.3%) pts. Conclusions: GLM significantly improves signs and symptoms in pts with moderate or severe RA responding inadequately to ETN or ADA. Over a third of pts achieved an ACR20 and over half achieved a DAS28-defined EULAR response beyond the results with their previous therapy. No difference was observed between IV and SC GLM. GLM was safe and well-tolerated. Disclosure of Interest: : J. Huffstutter Grant/research support: Amgen, Janssen, and Pfizer., Speakers bureau: Janssen and UCB., S. Kafka Grant/research support: same companies, as well as Lilly, Speakers bureau: Pfizer, Abbvie, Janssen, Amgen, BMS, Genentech, UCB, L. Brent Grant/research support: Janssen, Speakers bureau: AbbVie, Genentech, M. Matucci-Cerinic Grant/research support: Janssen, K. Tang Employee of: Janssen Research & Development, LLC., J. Wang Employee of: Janssen Research & Development, LLC., D. Decktor Employee of: Janssen Scientific Affairs, M. Chevrier Employee of: Janssen Scientific Affairs, T. Sprabery Employee of: Janssen Scientific Affairs, R. DeHoratius Employee of: Janssen Scientific Affairs DOI: 10.1136/annrheumdis-2014-eular.3766